2006
DOI: 10.1001/archneur.63.1.49
|View full text |Cite
|
Sign up to set email alerts
|

A 24-Week Open-Label Extension Study of Memantine in Moderate to Severe Alzheimer Disease

Abstract: Background: This study is an extension of a 28-week, randomized, double-blind, placebo-controlled study of memantine in 252 patients with moderate to severe Alzheimer disease.Objective: To evaluate long-term memantine treatment in moderate to severe Alzheimer disease.Design, Setting, and Patients: Open-label, 24-week extension trial. Raters remained blind to the patients' initial study treatment. Patients (n=175) were enrolled from the previous double-blind study in an outpatient setting.Intervention: Twenty m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(113 citation statements)
references
References 20 publications
6
99
0
8
Order By: Relevance
“…A␤ oligomers have also been shown to interfere with NMDA-R and postsynaptic AMPA-R, affecting synaptic function, calcium influx, and a number of downstream cascades [13]. The idea that cell death in AD is associated with over-activity of NMDA-R provides part of the basis for the use of the low affinity activitydependent NMDA-R antagonist, memantine, to treat this pathology [67]. In the present study, we show that both AMPA-R and NMDA-R, but not voltagegated calcium channels, are involved in the early disruption of Ca 2+ homeostasis induced by toxic A␤ oligomers (A+).…”
Section: Discussionmentioning
confidence: 99%
“…A␤ oligomers have also been shown to interfere with NMDA-R and postsynaptic AMPA-R, affecting synaptic function, calcium influx, and a number of downstream cascades [13]. The idea that cell death in AD is associated with over-activity of NMDA-R provides part of the basis for the use of the low affinity activitydependent NMDA-R antagonist, memantine, to treat this pathology [67]. In the present study, we show that both AMPA-R and NMDA-R, but not voltagegated calcium channels, are involved in the early disruption of Ca 2+ homeostasis induced by toxic A␤ oligomers (A+).…”
Section: Discussionmentioning
confidence: 99%
“…The manufacturer recommends twice-daily dosing, and it does not require regular laboratory monitoring. Several trials have shown that memantine is safe and results in modest improvements in cognition and behavior in patients with moderate-to-severe AD [121,122]. Earlier studies suggested that memantine was beneficial for patients with vascular dementia [208]; but, a recent meta-analysis of available research could not find a clinically detectable difference at 6 months for mild-to-moderate vascular dementia.…”
Section: Memantine: Memantine Was Approved For Ad Therapy In 2003 a mentioning
confidence: 99%
“…Previous studies, for example, are focused on the use of NMDAR antagonists, like memantine or (+) MK-801 as AD treatments [29,30]. In fact, memantine is one of the few FDA approved drugs for AD [43,44].…”
Section: Discussionmentioning
confidence: 99%